2013
DOI: 10.1097/dcc.0b013e31828083a4
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Stress, and Retention of Nurses in Critical Care

Abstract: Providing care to patients in critical care units generates stress. Helping the critical care nurse manage this stress can lead to better patient experiences and higher nursing retention. While providing holistic care to patients produces better outcomes, addressing the holistic needs of the caregiver must also be considered. Included in the holistic needs of the nurse is their spiritual well-being. A study that measures spiritual well-being, stress, and nursing retention is the focus of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…Critical care nurses are at high risk of intense fatigue and anxiety, with no assurance their patients will recover despite their best efforts at patient‐centred nursing (Menzies , Davidson et al . , Campbell ).…”
Section: Discussionmentioning
confidence: 99%
“…Critical care nurses are at high risk of intense fatigue and anxiety, with no assurance their patients will recover despite their best efforts at patient‐centred nursing (Menzies , Davidson et al . , Campbell ).…”
Section: Discussionmentioning
confidence: 99%
“…The health promotion actions carried out by nurses in patient care in the Intensive Care Unit are diverse and focused on the care indicated in the most recent studies on health promotion, thus raising the frequency of the following care, as shown in Table 1: decubitus position change (18), medication check before administration (7), talking to patients during procedures even if they do not demonstrate to understand (4), quiet environment (11) and oral health care (18).…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to identify broader problems, assist the individual to the fullest, with a view to meeting the demonstrated needs, evaluating the assistance provided and ensuring the effectiveness of his recovery. 7,8 The nurses stated that they did not have difficulty in carrying out health promotion activities, as well as there is no work overload that makes it impossible to carry out this care. All nurses affirm the existence of encouragement by team members to carry out health promotion to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, professional identity and workplace social capital have been found to promote positive outcomes (Kowalski et al, 2010; Middleton et al, 2018; Rasmussen et al, 2018; Sheingold & Sheingold, 2013; Shin & Lee, 2016; Zhang et al, 2017). However, the experience of stress can reduce the meaning perceived by nurses at work (Monnot & Beehr, 2014), as well as their job retention and nursing quality (Campbell, 2013). These findings provide evidence to suggest that the experience of stress will reduce the benefits that nurses receive from having high levels of professional identity.…”
Section: Figurementioning
confidence: 99%